2008
DOI: 10.2337/dc08-0618
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Parental History of Type 2 Diabetes and Glycemic Control in Urban African Americans

Abstract: OBJECTIVE —The purpose of this study was to examine the association between parental history of type 2 diabetes and glycemic control among diabetic urban African Americans. RESEARCH DESIGN AND METHODS —Study participants included 359 African Americans with type 2 diabetes from Baltimore, Maryland, enrolled in Project Sugar 2. Participants underwent an interview-administrated questionnaire that asked about family history, sociodemographics, clinical characteristics, and knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
2
13
3
1
Order By: Relevance
“…Our results suggest that the patients with a family history of diabetes may be more associated with atherogenic lipid profiles, which are not typical in type 2 diabetic patients. Unlike a previous report [21] showing inadequate glycemic control in patients with a family history of diabetes, our results showed that there were no significant differences in glycemic control between the patients with a family history of diabetes and those without a family history. It is noteworthy, in our study, that the degree of glycemic control was not affected by the strength of a family history, despite the significant difference of diabetes duration and fasting plasma C-peptide concentrations.…”
Section: Discussioncontrasting
confidence: 56%
“…Our results suggest that the patients with a family history of diabetes may be more associated with atherogenic lipid profiles, which are not typical in type 2 diabetic patients. Unlike a previous report [21] showing inadequate glycemic control in patients with a family history of diabetes, our results showed that there were no significant differences in glycemic control between the patients with a family history of diabetes and those without a family history. It is noteworthy, in our study, that the degree of glycemic control was not affected by the strength of a family history, despite the significant difference of diabetes duration and fasting plasma C-peptide concentrations.…”
Section: Discussioncontrasting
confidence: 56%
“…39 Our results also support a recent study examining the association between parental history of T2DM and glycemic control. 40 So we conclude that obtaining the family history of the disease is crucial in identifying and targeting high-risk patients with diabetes who may require more stringent lifestyle changes as well as pharmaceutical intervention.…”
mentioning
confidence: 97%
“…Patients with familial diabetes have relatively poor glycemic control, but few other clinical differences have been reported (4,5,9,10). An early age of onset and poor glycemic control would both be expected to have a negative impact on the development of chronic complications, but no such longitudinal data have been published.…”
mentioning
confidence: 99%